In Our Own Backyard: Principles for Effective Improvement of the Nation's Infrastructure - National Research Council
This volume takes a fresh look2014primarily from a technological perspective2014at the nation's \

Building for Tomorrow: Global Enterprise and the U.S. Construction Industry - National Research Council (The National Academies Press, 1988)

Practical Lessons from the Loma Prieta Earthquake - National Research Council (The National Academies Press, 1994)
The Loma Prieta earthquake struck the San Francisco area on October 17, 1989, causing 63 deaths and 10 billion worth of damage. This book reviews existing research on the Loma Prieta quake and draws from it practical lessons that could be applied to other earthquake-prone areas of the country. The volume contains seven keynote papers presented at a symposium on the earthquake and includes an overview written by the committee offering recommendations to improve seismic safety and earthquake awareness in parts of the country susceptible to earthquakes.

New Directions for Understanding Systemic Risk: A Report on a Conference Cosponsored by the Federal Reserve Bank of New York and the National Academy of Sciences - National Research Council (The National Academies Press, 2007)
The stability of the financial system and the potential for systemic events to alter its function have long been critical issues for central bankers and researchers. Recent events suggest that older models of systemic shocks might no longer capture all of the possible paths of such disturbances or account for the increasing complexity of the financial system. To help assess these concerns, the Federal Reserve Bank of New York and the NRC cosponsored a conference that brought together engineers, scientists, economists, and financial market experts to promote better understanding of systemic risk in a variety of fields. The book presents an examination of tools used in ecology and engineering to study systemic collapse in those areas; a review of current trends in economic research on systemic risk, the payments system, and the market of interbank funds; and for context, descriptions of how systemic risk in the financial system affects trading activities.

Responding to Changes in Sea Level: Engineering Implications - National Research Council (The National Academies Press, 1987)
Over the last 100 years, sea level has risen approximately 12 centimeters and is expected to continue rising at an even faster rate. This situation has serious implications for human activity along our coasts. In this book, geological and coastal engineering experts examine recent sea level trends and project changes over the next 100 years, anticipating shoreline response to changing sea level and the consequences for coastal development and uses. Scenarios for future sea level rise and several case studies are presented.

Technology for the United States Navy and Marine Corps, 2000-2035: Becoming a 21st-Century Force: Volume 9: Modeling and Simulation - National Research Council (The National Academies Press, 1997)

High-Performance Bolting Technology for Offshore Oil and Natural Gas Operations - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Commercially significant amounts of crude oil and natural gas lie under the continental shelf of the United States. Advances in locating deposits, and improvements in drilling and recovery technology, have made it technically and economically feasible to extract these resources under harsh conditions. But extracting these offshore petroleum resources involves the possibility, however remote, of oil spills, with resulting damage to the ocean and the coastline ecosystems and risks to life and limb of those performing the extraction. The environmental consequences of an oil spill can be more severe underwater than on land because sea currents can quickly disperse the oil over a large area and, thus, cleanup can be problematic. Bolted connections are an integral feature of deep-water well operations. High-Performance Bolting Technology for Offshore Oil and Natural Gas Operations summarizes strategies for improving the reliability of fasteners used in offshore oil exploration equipment, as well as best practices from other industrial sectors. It focuses on critical bolting2014bolts, studs, nuts, and fasteners used on critical connections.